2014
DOI: 10.5586/asbp.2014.019
|View full text |Cite
|
Sign up to set email alerts
|

The detection of thermophilous forest hotspots in Poland using geostatistical interpolation of plant richness

Abstract: Attempts to study biodiversity hotspots on a regional scale should combine compositional and functionalist criteria. The detection of hotspots in this study uses one ecologically similar group of high conservation value species as hotspot indicators, as well as focal habitat indicators, to detect the distribution of suitable environmental conditions. The method is assessed with reference to thermophilous forests in Poland -key habitats for many rare and relict species. Twenty-six high conservation priority spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…In the Polish part of the Sudetes (SW Poland), thermophilous oak forests, which occupy approximately 3000 ha (Szymura ), have not been coppiced since the end of War World II. At the same time, they are still considered one of the forest communities richest in species in Poland, and their role in the protection of biodiversity is considered to be crucial (Kiedrzyński & Jakubowska‐Gabara ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Polish part of the Sudetes (SW Poland), thermophilous oak forests, which occupy approximately 3000 ha (Szymura ), have not been coppiced since the end of War World II. At the same time, they are still considered one of the forest communities richest in species in Poland, and their role in the protection of biodiversity is considered to be crucial (Kiedrzyński & Jakubowska‐Gabara ).…”
Section: Introductionmentioning
confidence: 99%
“…As listed in Annex II (b) of the Habitats Directive (Anonymous1992) is considered a plant species of European Community interest whose conservation requires designation of special areas of conservation (Natura 2000 sites). Moreover, it is considered species indicator of thermophilous forest hotspots signaling remnant pools of biodiversity (Kiedrzyński & Jakubowska-Gabara 2014). Species conservation status at European level was assessed as "Unfavourable bad", for both reporting periods (2001-2006 and 2007-2012) under article 17 of Habitats Directive (European Topic Centre on Biological Diversity).…”
Section: Introductionmentioning
confidence: 99%
“…However, the population in Góra Krzemyk, which occurs under the beech trees, is located on the hill slope and near the edge of the forest, where the light is also well available (at least for some individuals in population). Moreover, the additional plant height measurements done in the region showed that the maximum growth of A. europaea in the oak forest in the Korzecko locality (more than 40 km away from studied populations) did not exceed 220 cm (Kiedrzyński 2014, unpublished data). Furthermore, observations of A. europaea in the Botanical Garden of the Faculty of Biology and Environmental Protection at the University of Lodz, where they were planted in 1985 and have grown in full light conditions, indicated that the tallest shoots did not exceed 235 cm (Kiedrzyński 2013-15, unpublished data).…”
Section: Resultsmentioning
confidence: 87%
“…The occurrence of Actaea europaea in Poland corresponds with the location of hotspots of thermophilous forest fl ora [6]. In 2011, a large population of C. europaea was discovered in central Poland [5] at the westernmost extent of its range in Europe.…”
mentioning
confidence: 99%